Identifying Spatial Efficiency–Equity Tradeoffs in Territorial Development Policies : Evidence from Uganda - Lall, Somik V.; Schroeder, Elizabeth; Schmidt, Emily (2012)
In many countries, place specific investments in infrastructure are viewed as integral components of territorial development policies. But are these policies fighting market forces of concentration? Or are they adding net value to the national economy by tapping underexploited resources? This paper contributes to the debate on the spatial allocation of infrastructure investments by examining where these investments will generate the highest economic returns "spatial efficiency", and identifying whether there re tradeoffs when infrastructure coverage is made more equitable across regions "spatial equity". The empirical analysis focuses on Uganda and is based on estimating models of firm location choice, drawing on insights from the new economic geography literature. The main findings show that establishments in the manufacturing industry gain from being in areas that offer a diverse mix of economic activities. In addition, availability of power supply, transport links connecting districts to markets, and the supply of skilled workers attract manufacturing activities. Combining all these factors gives a distinct advantage to existing agglomerations along leading areas around Kampala and Jinja. Infrastructure investments in these areas are likely to produce the highest returns compared with investments elsewhere. Public infrastructure investments in other locations are likely to attract fewer private investors, and will pose a spatial efficiencyequity tradeoff. To better integrate lagging regions with the national economy, lessons from the WDR2009 "Reshaping Economic Geography" calling for investments in health and education in lagging areas are likely to be more beneficial.